The Soothing Effects of Shirodhara: Alleviating Stress through an Ancient Ayurvedic Technique - Rajan, Sujata; Deshmukh, P U; Pawar, Jatved; Shamkuwar, Manoj; Kaur, Jaspreet; Jakhar, Neelam (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Shirodhara therapy, an ancient Ayurvedic practice, is gaining recognition as a potential stress management tool. This therapy involves the gentle pouring of warm herbal oil or other soothing liquids onto the forehead, inducing deep relaxation. As stress-related disorders continue to rise, exploring effective and alternative approaches like Shirodhara is crucial. Methods: This article reviews existing scientific literature and clinical studies to evaluate the effectiveness of Shirodhara therapy in stress reduction. Research papers, systematic reviews, and meta-analyses were examined to gather relevant data on the physiological and psychological effects of Shirodhara in stress management. Results: The findings from the reviewed studies suggest that Shirodhara therapy exhibits a significant promise in alleviating stress and its associated symptoms. It has been shown to balance stress hormones, activate the body’s relaxation response, and induce a profound sense of calmness. Moreover, Shirodhara has demonstrated positive outcomes in reducing anxiety levels, improving sleep quality, and lowering blood pressure. Conclusion: Shirodhara therapy offers a holistic and natural alternative for stress management, with promising results seen in various studies. Its potential integration into mainstream practices is promising. However, further research is needed to understand mechanisms, optimize protocols, and assess long-term efficacy. This emerging field provides exciting opportunities to explore Shirodhara’s therapeutic potential in addressing stress-related disorders.